Evaluation of Collapsibility of Compacted Loess Based on Resistivity Index - Yongpeng Nie; Wankui Ni; Haiman Wang; Kangze Yuan; Wenxin Tuo; Xiangning Li (Advances in Materials Science and Engineering)
Recently, a lot of engineering constructions have been carried out in the Loess Plateau of China. However, the collapsibility of compacted loess as a filler poses a potential threat to the safety and stability of buildings. To address this threat, the scientific evaluation of the collapsibility of compacted loess has become a key to engineering construction. This study, therefore, tested the resistivity of compacted loess under varying conditions of water content, dry density, and its collapsibility coefficient under a pressure of 200 kPa. The correlation between collapsibility and electrical parameters was determined, and based on the resistivity, a new method to evaluate the collapsibility of the compacted loess is proposed. The results show that the resistivity of compacted loess decreases with an increase in water content and dry density and that the effect of water content is more significant. There is a critical water content value that causes the resistivity decay rate to slow down. The collapsibility coefficient also decreases with an increase in water content and dry density, and under the same dry density or same water content, the collapsibility coefficient and resistivity are positively correlated. According to the normalized resistivity value ρ/ρw, the relative collapsibility coefficient δs /0.015, and the water content ω obtained in the experiment, a collapsibility coefficient prediction model based on the resistivity of compacted loess was established. Using resistivity to evaluate the collapsibility of loess is nondestructive and provides a new method to accurately and quickly evaluate the collapsibility of compacted loess.